Serum Uric Acid Is Associated With Coronary Artery Calcification. Issue 6 (16th April 2014) - Grossman, Chagai; Shemesh, Joseph; Koren‐Morag, Nira; Bornstein, Gil; Ben‐Zvi, Ilan; Grossman, Ehud
<x xml:space="preserve">Abstract</x> Uric acid (UA) is associated with atherosclerosis, and coronary artery calcium (CAC) is a marker of atherosclerosis. The authors studied the association between UA and CAC. A total of 663 asymptomatic patients (564 men; mean age, 55±7 years) were evaluated for the presence of CAC. The study population was divided into three tertiles according to their UA levels, and the prevalence of CAC was compared between the tertiles. CAC was detected in 349 (53%) patients. Levels of UA were significantly higher in those with CAC than in those without CAC (5.6+1.2 vs 5.3+1.3; P=.003). The odds ratio for the presence of CAC in the highest vs lowest UA tertile was 1.72 (95% confidence interval, 1.17–2.51). The highest UA tertile remained associated with the presence of CAC after adjustment for known cardiovascular risk factors. The results show that high serum UA levels are associated with the presence of CAC.